Analysis of the Customs Supervision System in the Batam Free Trade Zone - Nareswari, Aisya; Susanto, Nurhadi (CV. Publikasi Indonesia, 2025)
This study examines the weaknesses of the customs supervision system in the Batam Free Trade Zone (FTZ) and its implications for Indonesia’s domestic market. As a free trade area with a high volume of imported goods, Batam FTZ contains structural vulnerabilities that may be exploited for smuggling and the evasion of fiscal obligations. Using a qualitative approach, this research draws on interviews with customs officers, business operators, and customs service providers, complemented by a literature review to identify risk factors and supervisory gaps. The findings indicate that shortcomings in the supervision system stem from limited human resources, inadequate inter-agency data integration, the use of small and difficult-to-monitor ports, and significant information asymmetry between authorities and economic actors. These gaps contribute to increased risks of fiscal leakage and the circulation of unmonitored goods in the domestic market, which can disrupt price stability and fair competition. The study concludes that customs supervision in the Batam FTZ remains suboptimal and requires strengthened institutional capacity, enhanced internal controls, and the development of real-time, technology-based monitoring systems to reduce violations and maintain domestic market stability.